COLOUR DOPPLER INDICES OF OVARIAN ARTERY IN RELATION TO OVARIAN ACTIVITY IN CROSSBRED CATTLE - SATHESHKUMAR, S; SIVAKUMAR, A; RAJA, S; JAYAGANTHAN, P; PRABAHARAN, V; RAJASUNDARAM, RC (The Indian Journal of Animal Reproduction, 2017)
Crossbred cattle exhibiting estrus or post-partum anestrus were subjected to colour doppler ultrasonography to evaluate the blood flow parameters viz., peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI), resistivity index (RI) and doppler pulse duration (DPD). The comparison of blood flow parameters of cattle in estrus (n=12) revealed that PSV and DPD indices in dominant follicle and ipsilateral ovarian artery were highly correlated (p
Keywords: Anestrus; Cattle; Colour doppler; Doppler indices; Ovarian artery